Pengaruh Akupresure Titik PC6 Dalam Mengurangi Emesis Gravidarum - Anik Triatmini; Kamidah Kamidah (Pusat Riset dan Inovasi Nasional, 2023)
Background; Emesis gravidarum is a physiological thing but if it is not treated immediately it will become a pathological thing. Most emesis gravidarum can be treated with outpatient treatment, but a small number of pregnant women cannot cope with nausea and vomiting, so that it interferes with their daily activities and falls into a condition called hyperemia gravidarium. From these problems can be overcome by being given a treatment that can reduce nausea and vomiting in pregnant women in the first trimester, namely PC6 acupressure point. Objective; Knowing the effect of PC6 point acupressure on reducing the frequency of emesis gravidarum. Method; In this study using a quantitative design with an experimental approach to the design of one group pre test post test. The data analysis technique uses the Wilcoxon test. Sample; the sampling technique used in this study was quota sampling with a sample size of 28 respondents. Results; Based on the results of the analysis with the Wilcoxon test, the p value was obtained - 0.000 or (0.000) < (-0.05) then H0 was rejected and H1 was accepted. So it can be concluded that there is an effect of PC6 acupressure on the frequency of Emesis gravidarum in first trimester pregnant women at the Independent Practice of Midwife Yohana Puspiyati A.Md Keb Mukiran, Kaliwungu, Semarang. Conclusion; There was a decrease in emesis gravidarium after PC6 point acupressure was performed on first trimester pregnant women.